(untitled) (Journal of Atomic and Molecular Sciences, 2016)
We use time-dependent density functional theory together with a set of extensive multidimensional visualization techniques to characterize the field-dependent electronic structure and rate of photo-induced charge transfer in organic donor-acceptor dyad. External electric field is incorporated into the generalized Mulliken-Hush model and Marcus theory. We use these methods to evaluate the influence of the external electric field on the electronic coupling between donor and acceptor. We also calculate the reorganization energy and the free energy change of the electron transfer. These theoretical methods and calculation techniques proves that the external electric field has main effect on the electron transfer rate. More important, our results provide a new framework to understand charge transfer of organic systems under the external electric field.